Macramé : the craft of creative knotting for your home - Zedenius, Fanny (Quadrille Publishing, 2017)
"Swedish designer Fanny Zedenius has revitalised the art of macramé, giving this nostalgic craft a modern twist. Macramé features a collection of over 20 beautifully designed projects to make for your home, as well as everything you need to know to master the art of creative knotting. With just your hands and some lengths of rope, you can make macramé plant hangars, wall hangings, dream catchers and more. Macramé truly is a craft for all, regardless of ability, and Fanny's delightful book will provide you with all the tools to pick up the ropes"--Back cover.